Insights into Population Genetics and Phylogeography of Mycobacterium tuberculosis - B. A. Tkhorenko; A. V. Meyer; T. V. Pyanzova; A. V. Lyamin; M. B. Lavryashina (Туберкулез и болезни лёгких, 2024)
The review summarizes the current understanding of population genetics and genetic classification of Mycobacterium tuberculosis. Articles accumulated in Elibrary and PubMed were used as a source of information. Using keywords, more than 100 publications were found and analyzed for the period from 2009 to 2023, 35 of which were included in the review. According to the current concept, M. tuberculosis is represented by nine lineages (superfamilies L1-L9), each of which has different characteristics of evolutionary status, genetic diversity, transmissibility, drug resistance, latency, and vaccine effectiveness.